1999
DOI: 10.1002/(sici)1097-0231(19991115)13:21<2166::aid-rcm770>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the instrumental detection limits of commercial nonylphenol ethoxylates with a wide range of molecular masses using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Recent interest in the environmental fate and impact of nonylphenol ethoxylates (NPEs) has necessitated the need for the development of specific, and yet efficient, analytical methodologies for their detection. Using seventeen commercial NPEs, all having the general formula 4-(C(9)H(19))-C(6)H(4)-(OCH(2)CH(2))(n)-OH, we have established minimum concentrations at which matrix-assisted laser desorption ionization (MALDI)/time-of-flight (TOF)/mass spectrometry (MS) can be used in their detection. The NPEs were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…However, observation of the molecular ion became increasingly difficult as the molecular weight of the conjugates increased and the degree of branching decreased. This is presumably due to the increased sublimation energies of the high MW polymers, leading to a decrease in their concentrations in the gaseous plume reaching the detector …”
Section: Resultsmentioning
confidence: 99%
“…However, observation of the molecular ion became increasingly difficult as the molecular weight of the conjugates increased and the degree of branching decreased. This is presumably due to the increased sublimation energies of the high MW polymers, leading to a decrease in their concentrations in the gaseous plume reaching the detector …”
Section: Resultsmentioning
confidence: 99%
“…We recently reported on the use of MALDI‐TOFMS in the analysis of complex formulations that include lipids, nonionic surfactants, polysorbates, fatty acids, and porphyrins 9–13. These studies have shown that the mode of ionization varies with the different classes of chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…Ayorinde and Elhila have found that instrumental detection limits for NPEs are directly dependent on molecular weight. Low molecular weight NPEs were detectable at 10 µg/L, and higher molecular weight NPEs show detection limits as high as 4.5 mg/L [70].…”
Section: Qualitative Characterization Of Lmw Compoundsmentioning
confidence: 96%